Ensaios ecotoxicológicos utilizando Chlorella vulgaris para análise de anti-hipertensivos - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá, 2023)
Population growth, inadequate basic sanitation and poor water treatment are factors that contribute to the presence of emerging contaminants. These contaminants come from different sources such as cleaning and hygiene products, pesticides and medicines that go to aquatic environments and even very small concentrations can promote changes in the aquatic community. Ecotoxicology studies impacts and their possible effects on the environment and organisms. This study analyzed possible effects of antihypertensive drugs, a class of medication widely used by the population, on the aquatic biota. The chosen test organism was Chlorella vulgaris and the effects on its growth curve were evaluated. Five antihypertensive drugs were selected: Hydrochlorothiazide, Atenolol, Enalapril maleate, Captopril and Losartan and the methodology used for ecotoxicological tests was the protocol established by ABNT. The results of the tests showed, in general, that both in acute and chronic exposure, there was a reduction in growth when compared to the control sample, revealing an inhibitory effect of antihypertensive drugs on the growth of Chlorella vulgaris. This microalgae is a primary producer and the reduction in growth may indicate a possible decrease in the production of biomass that serves as food mainly for fish in their early stages of development. The lack of this food source can lead to a decrease in fish production, directly affecting their growth. |In this way, it is extremely important that new studies on the presence of emerging pollutants are carried out. Pharmaceutical has a essential function in helping to prevent this problem, as they can guide the population to properly dispose of these medications and warn about the problems that improper disposal can cause in the environment and human health.
Keywords: Ecotoxicologia; Anti-hipertensivos; Chlorella vulgaris; Poluentes emergentes; CNPQ::CIENCIAS DA SAUDE::FARMACIA; ODS 3 – Saúde e bem-estar; ODS 6 – Água potável e saneamento; ODS 12 – Consumo e produção responsáveis